Analytical methods for energy diversity and security : portfolio optimization in the energy sector: a tribute to the work of Dr Shimon Awerbuch /: portfolio optimization in the energy sector: a tribute to the work of Dr Shimon Awerbuch. (2009) - Unknown
No abstract available